Pengaruh Tingkat Pendidikan, Kesehatan, dan Pertumbuhan Ekonomi terhadap Jumlah Penduduk Miskin di Kabupaten Tanah Laut - Siti Fatimah; Choirul Sa’roni (PPJP ULM, 2020)
This study aims to determine the magnitude of education level, health, and economicgrowth both simultaneously and partially on the number of people deficient in theDistrict of Tanah Laut in 2010 – 2018. The data used in secondary data is sourced fromthe Central Statistic Agency in Tanah Laut District. The data analysis technique used inmultiple regression analysis. Test results using Eviews 10 obtained the results ofeducation level, health, and economic growth simultaneously had a significant effect onthe number of people deficient in the District of Tanah Laut. Whereas partially ofeducation level has a negative and significant impact, health is the most dominantfactor. It has a positive and significant effect, and economic growth has an insignificantimpact on the number of people deficient in the District of Tanah Laut.